Headspace Determination of Acetone and Aromatic Hydrocarbons in Soil Using a Homebuilt, Inexpensive Gas Chromatograph with Photoionization Detection - Cameron Shane; Carly M. Kennell; Michael J. Geyer; Thomas N. Loegel; Neil D. Danielson (Separations)
We have designed, built, and characterized an inexpensive gas chromatograph with photoionization detection using readily commercially available components. These include a home carbonation CO2 cylinder for the carrier gas, headspace sampling using a low pressure six port valve, a standard 30 m wide-bore capillary column, a consumer convection oven including added insulation with a thermocouple, and a photoionization sensor enclosed in a flow cell. The chromatography retention time reproducibility is good due to temperature control within 0.5 °C. The headspace linearity response using a 0.5 mL injection of benzene was from 10 to 250 ppm, with the limit of detection estimated at 4 ppm. The application of this instrument to the headspace monitoring of four soil samples spiked with a commercial adhesive cleaner containing acetone, ethyl benzene, and xylenes was possible. The interaction of acetone with the two different potting soil samples, likely due to their high organic content, was persistent for at least 30 min, even above an ambient temperature (60 °C). A comparison of linear plots of the signal versus volatilization time over the first 20 min showed substantially larger slopes for the two yard soil samples, indicating the rapid volatilization of acetone from these lower organic content soils, as compared to the two potting soil samples. This GC-PID instrument can be considered portable because it can be easily taken apart, transported, and reassembled. One viable option for the extension of the applications of this instrument is to provide hands-on teaching of GC.